2021
DOI: 10.3390/ijerph18031006
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Profiles and Self-Esteem/Self-Concept: An Analysis of Relationships in Gifted Students

Abstract: The psychological well-being of students affects their academic achievement, social relationships and school coexistence and is something that families worry about. This aspect becomes vital when students have atypical development and/or specific needs. Studies on the impact of giftedness on students’ self-concept and self-esteem offer mixed results. Emotional Intelligence (EI) is a key factor for their well-being that must be developed by educational institutions. This study analyzes the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 112 publications
(201 reference statements)
1
18
0
8
Order By: Relevance
“…Within the group of gifted students, levels of well-being were higher for those who were nominated by their teachers as gifted students and showed high academic achievement. Casino-García et al (2021) found significantly lower scores for family, social, and physical self-concepts and for self-esteem in gifted children and adolescents aged 8 to 18 years. However, the scientific literature presents contradictory results (Hoge and Renzulli, 1993;Neihart, 1999;Litster and Roberts, 2011).…”
Section: The Well-being Of Gifted Studentsmentioning
confidence: 75%
“…Within the group of gifted students, levels of well-being were higher for those who were nominated by their teachers as gifted students and showed high academic achievement. Casino-García et al (2021) found significantly lower scores for family, social, and physical self-concepts and for self-esteem in gifted children and adolescents aged 8 to 18 years. However, the scientific literature presents contradictory results (Hoge and Renzulli, 1993;Neihart, 1999;Litster and Roberts, 2011).…”
Section: The Well-being Of Gifted Studentsmentioning
confidence: 75%
“…All children have a fundamental psychological need to be a part of a group and to be accepted by their peers, as well as to form and sustain long-term interpersonal relationships. This need is profound during childhood, when one of the greatest challenges is establishing secure friendships [27]. Most of the children in the current study were categorized as having a moderate level of self-esteem, as rated by their teachers.…”
Section: Discussionmentioning
confidence: 95%
“…Empirical studies of self-esteem and giftedness have highlighted that self-esteem is a catalyst in the process of talent development [27] and is positively correlated with motivation and superior academic outcomes [28]. However, results of studies of self-esteem in gifted children are varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de las posibilidades que la IE puede brindar al alumnado, a las familias y al personal docente (Casino-García et al, 2021;Chen y Guo, 2020), existen trabajos como el de García-Retana (2012) a través del que se reflexiona sobre cómo, a lo largo del tiempo, ha existido en el contexto escolar una tendencia por priorizar el componente cognitivo al emocional. Sin embargo, son numerosos los centros educativos de enseñanzas obligatorias que trabajan la IE dentro de sus jornadas escolares.…”
Section: La Educación De La Inteligencia Emocionalunclassified